ANALISIS PROGRAM KEMITRAAN CSR PT. TELEKOMUNIKASI INDONESIA DALAM UPAYA PENINGKATAN KINERJA UMKM (Studi Pada UMKM Mitra Binaan PT. Telkom Witel Semarang) - Christina Dessy Permatasari; Bulan Prabawani (Universitas Diponegoro, 2021)
Abstract: PT. Telkom is one of the state-owned companies trying to build trust by using the strategy of developing CSR programs. Telkom has also thought about no longer working solely to get the maximum profit, but is more inclined towards building long-term business sustainability and empowering the community (community development). Based on interviews with the staff of the CDC Unit PT. Telkom Witel Semarang, the results of the evaluation of MSMEs Andjani and Wingko